Avaliação triplanar do segmento acetabular após osteotomia pélvica tripla, fixada com dois tipos de placas ósseas, associada a desmotomia do sacrotuberal, com e sem fixação do segmento isquiático, em cadáveres de cães - Simões, Adriano (2009)
Hip dysplasia is a disease that affects animals in growth, resulting from malformation of the coxofemoral joint, causing biomechanical disturbance between the femoral head and acetabulum, leading to degenerative and progressive joint disease. The aim of this study was to evaluate the technique of triple pelvic osteotomy (TPO), six pelvis of adult dogs weighing between 30 and 40kg, not dysplastic, using two groups of bony plates of stainless steel for the specific technique of TPO divided into two groups: Group 1 (GI) three plates of New Generation ® Devices with preset angles of 20 °, 30 ° and 40 ° and Group 2 (GII) three plates of the Orthopedic Vet ® also with the same preset angles . Measuring it in five different moments in the real angle pieces performed by each plate with and without fixing the sciatic segment and with and without desmotomy sacrotuberal by photographic analysis triplanar and ventro-dorsal radiograph. The variables analysed by the photographic images were: degree of axial rotation of the acetabular segment GRASA, ventro-dorsal deviation of the acetabular segment (DVDSA), medial-lateral deviation of the acetabular segment (DMLSA) and the ventro-dorsal radiographic images of the pieces was measured the percentage of coverage of the femoral head (PCCCF). The results of the variables were: GRASA that showed a significant increase after the placement of signs of GI and GII; DVDSA was to curb the use of cerclage in the segment sciatic; DMLSA wich was significant with the desmotomy sacrotuberal associatedwith not fixing the sciatic segment with cerclage and PCCCF where it was noted significant variations in the placement of plates 20°, 30° and 40° in GI and GII with increased coverage in the moments following the femoral OPT. There was no significant difference between GI and GII within and between each time of evaluation for any of the variables studied. And it was concluded that the plate with angulation of 20°, as both the GI and GII, with cerclage promoted the establishment of axial rotation of the acetabular segment with significant variation in the percentage of femoral head coverage promoting concomitantly, smaller changes in ventraldorsal deviation and mid-lateral acetabular segment when compared to the plates with angle of 30° and 40°.